Transaction Costs, Order Placement Strategy, and Existence of the Bid-Ask Spread - Cohen, Kalman J.; Maier, Steven F.; Schwartz, Robert A.; Whitcomb, David K. (Journal of Political Economy, 1981)
By considering investor order placement strategy, this paper demonstrates that transaction costs cause bid-ask spreads to be an equilibrium property of asset markets. With transaction costs, the probability of a limit order executing does not go to unity as the order is placed infinitesimally close to a counterpart market quote; thus, with certainty of execution at the counterpart market quote, a "gravitational pull" is generated that keeps counterpart quotes from being placed infinitesimally close to each other. An equilibrium spread is defined and its size linked to market thinness; implications are noted for the design of a trading system.